Virtual Testing Method of Human Knee Prosthesis - Kheireddine, Zehouani; Oldal, István (International Journal of Engineering and Management Sciences, 2019)
In the human knee joint, a degenerative wear of the joint can be formed, the common treatment of this disease is the total knee prosthesis geometry replacement and prosthesis implanting, the aim of our research is the study of the human knee joint with applications in prosthesis, we will develop a method by creating a virtual knee prosthesis geometries, we will generate the geometries using the ADAMS program and examined on a special knee prosthesis qualification equipment.